STANDAR OPERASIONAL PROSEDUR PELAYANAN MEDIASI DI KANTOR MAHKAMAH SYAR’IYAH SUKA MAKMUE NAGAN RAYA - Hamdi, Syaibatul; Efendi, Sumardi; Rahma, Ida; Anisah; Elita, Anggun Dian; Rahmawati; Widyana; Munirullah, Alfata; Rahmawati, Octavia (Faculty of Economics and Business Lampung University, 2024)
This Field Experience Practice discusses the implementation of the “Standard Operating Procedure for Mediation Services” at the Islamic Court of Suka Makmue, Nagan Raya. The primary focus of this practice is to introduce and familiarize students with standardized SOPs to guide the implementation of mediation in the Islamic judiciary environment. Through observation and active participation, students comprehend the stages of the mediation process, the role of the mediator, and how the SOP serves as the operational foundation ensuring consistency and effectiveness in dispute resolution. This practice successfully achieves its goal of applying theoretical knowledge in the practical context of the Islamic Court. Students deepen their understanding of the intricacies of mediation and enrich their knowledge about mediation services at the Islamic Court of Suka Makmue. By detailing the steps in the SOP, this practice provides a clear overview of how mediation is integrated as the primary approach in dispute resolution. The results indicate that the Islamic Court of Suka Makmue consistently adheres to legal foundations, such as Supreme Court Regulation Number 1 of 2016, mandating mediation before a trial. This Field Experience Practice makes a positive contribution to students' understanding of operational procedures and the principles of good governance embedded in mediation services at the Islamic Court.